Real Exchange Rate Response to Capital Inflows: a Dynamic Analysis for Sri Lanka - Sivakanthan, S.; Sooriyakumar, K.; Sireeranhan, A. (University of Jaffna, 2008)
One of the most challenging problems in developing countries such as Sri Lanka is exchange rate management. This study is assessing to identify the factors that influence the exchange rate of Sri Lankan money and nature of influence. Exchange rate is the value of one currency in relation to another currency. For this study, annual data were collected from 1959 to 2002 from central bank statistical report regarding exchange rate, terms of trade, foreign aid and trade liberalization. These data are time series data. The unit root test of stationary is used to test whether the time series data is stationary or non-stationary. Dickey-Fuller (DF) test and Augmented Dickey-Fuller (ADF) test are used for this. The first in this analysis was to establish the order of integration of the variables. This was done using the Augumented Dicky Fuller (ADF) test. To test for cointegration, Johansen Maximum Likelihood procedure was used. Augmented Dickey fuller test was used to establish the order of integration of the variables The result of this model reveals that higher the terms of trade tends to be associated with an increase in exchange rate. This means that when the price of export commodities increases relative to the price of imported commodities value of Sri Lankan currency will increase relative to US Dollar. The real exchange rate response of foreign aids shows that when foreign aid increases the demand for foreign currency decreases. Then, exchange rate of Sri Lankan currency increases. There is a negative relationship with exchange rate and the trade liberalization is as found in this analysis. This is because, after trade liberalization from 1977, the import has increased. In this case the decreases in exchange rate of Sri Lankan currency while other factors are held as fixed. Effective export promotional program and industrial development program will help to improve the exchange rate of Sri Lankan currency